Protective Effect of Exercise Preconditioning on Myocardial Ischemia-Reperfusion Injury in Rats Based on Autophagy - Qiang TANG; Jiyao ZHANG; Hongyu LI; Xue WANG; Xia YIN; Xuedong WANG; Zichen MU; Luwen ZHU (康复学报)
Objective:To explore the protective effect of exercise preconditioning on myocardial ischemia-reperfusion injury (MIRI) in rats and its mechanism based on autophagy.Methods:A total of 45 adult male Sprague-Dawley (SD) rats were randomly divided into model group (MIRI group), sham group (Sham group) and model+exercise preconditioning group (EP group), with 15 rats in each group. No myocardial ischemia-reperfusion were done in the Sham group. Left anterior descending coronary artery (LAD) was ligated in the MIRI group and EP group. Before modeling the Sham group and MIRI group didn't receive intervention, and the EP group was given electric treadmill training for four weeks. The ultrastructure and autophagic bodies of rat cardiac myocytes were observed by transmission electron microscopy, the infarct size was measured by Evans blue-TTC double staining, and the expression ofPI3K-Akt-mTOR signal pathway related proteins was detected by Western blot.Results:In the Sham group, the nuclear membrane was intact and continuous, the myofibrillar bundles arranged orderly, the structure of mitochondria was intact and no edema, the morphology of myocardial cells was normal, and no autophagic bodies were found; in the MIRI group, the myofibrillar bundles were loose and disordered with interstitial edema, mitochondria and myocardial cells were damaged seriously, the structure of cells was disordered, and autophagy was observed in the field of vision; in the EP group, some of sarcoplasmic reticulum was edema and expanding, mitochondrial structure was more complete with slight edema, myocardial cell was less damaged, and autophagy was less. The Sham group had no myocardial ischemia and infarction; compared with the MIRI group, the area of myocardial infarction in the EP group was significantly reduced, the difference was statistically significant (P< 0.05). Compared with the MIRI group, p-PI3K/PI3K and p-mTOR/mTOR in the EP group increased (P< 0.05).Conclusion:Exercise preconditioning has a significant protective effect on myocardial ischemia-reperfusion injury in rats. Its mechanism may be related to the activation of PI3K-Akt-mTOR signaling pathway to inhibit excessive autophagy.